Tipagem E Teste De Compatibilidade Sanguínea, Caracterização Hematológica E Bioquímica Em Felinos Selvagens E Domésticos - SILVA, Talita Dayane Pereira e (2011)
The neotropical felids are represented by ten species, having been Brazil eight host of these. These animals are constant victims of running over in highways and still they suffer with intense infestation for parasites, what it can result in intense anemia, being necessary the accomplishment of blood transfusion. In the present study blood samples were used of eight jaguarundies (Puma yagouaroundi), eight ocelots (Leopardus pardalis), seven pampas cats (Leopardus colocolo), seven domestic cats (Felis catus) of the Persian race and eight domestic cats (Felis catus) without definite race (SRD), whose aim was: a) to carry through blood typing and tests of compatibility between corresponding blood types in the different species; b) to carry through count blood cells (CBC), comparing the technique automatized by means of device BC - 2800 vet (software for domestic cats), with the manual technique for the wild species; and c) to carry through the profile biochemist and electrophoretic of serum proteins. In the typing, the occurrence of the blood type A was of 100% between ocelots, pampas cats and domestic cats Persian and of 85,72% between domestic cats SRD. 100% of the jaguarundies were type B and 14,28% of domestic cats SRD. To the tests of blood compatibility, 87,5% (n=4) of the ocelots were incompatible with domestic cats and 12,5% (n=1) were compatible; 100% (n= 6) of the pampas cats were compatible with domestic cats and 100% (n= 4) of the jaguarundies were incompatible with domestic cat of type B. It is concluded that in accordance with tests of blood compatibility the transfusion between domestic and pampas cats is possible, it is impossible the transfusion between domestic and jaguarundies and that more studies must be carried through for ocelots. In the comparison enters the techniques for the accomplishment of the CBC the automatized technique demonstrated statistical results equal for the majority of the parameters, also inside of the values of reference for the species, except in the counting of leukocytes of jaguarundies, whose resulted gotten for automation were bigger. It had good correlation between the techniques, mainly in the ocelot species. Concludes that device BC 2800 vet with the configuration for domestic cats is a technique fast and trustworthy in the accomplishment of blood cells count for species pampas cat and ocelot. The manual counting of leukocytes must be preferred for jaguarundies. The results gotten for many of the evaluated parameters biochemistries were similar to the described as values of reference for the studied species. However, the values found for ALT and AST were above of the values of reference for jaguarundies and ocelots. The value of glucose was above for the species pampas cat. The urea was above of the values of reference for the three species. The electrophoretic race for the analyzed species was similar to the described one for domestic cats contends albumen, alpha globulins (alpha 1 and 2), beta globulins (beta 1 and 2) and gamma globulins, however, in all the species had individuals that they had not presented beta globulin of the type beta 2. The gotten results can be used as normality parameters for the species pampas cat, ocelots and jaguarundies from Cerrado biome.